Unveiling the Carbon Footprint: Biomass vs. Geothermal Energy in Indonesia - Idroes, Ghalieb Mutig; Syahnur, Sofyan; Majid, M. Shabri Abd; Idroes, Rinadi; Kusumo, Fitranto; Hardi, Irsan (Ekonomikalia Journal of Economics, 2023)
Global climate change, caused by greenhouse gases (GHGs) emissions, particularly carbon dioxide (CO2), has an enormous and unprecedented impact on our planet's ecosystem, development, and long-term sustainability. This study investigates the dynamic impact of biomass and geothermal energy on CO2 emissions in Indonesia from 2000 to 2020. Employing the Green Solow model with the approach of Fully-Modified Ordinary Least Squares (FMOLS), Dynamic Ordinary Least Squares (DOLS), Autoregressive Distributed Lag (ARDL) and Pairwise Granger causality test. The cointegration tests suggest the existence of a long-term equilibrium relationship between CO2 emissions, biomass, and geothermal energy. Empirical evidence reveals that although biomass and geothermal energy positively influence CO2 emissions, their overall impact is relatively low. This highlights the potential for these renewable energy sources to contribute to CO2 reduction and promote environmental sustainability. The Granger causality test confirms a causal relationship between CO2 emissions, biomass, and geothermal energy. Important policy recommendations for promoting sustainable energy practices in Indonesia involve investing in high-quality biomass and geothermal facilities to reduce emissions, implementing energy efficiency programs and fossil fuel conservation measures, and encouraging the use of electricity-based biomass and geothermal energy sources to reduce dependence on non-renewable fuels. These recommendations play a crucial role in achieving environmental and economic sustainability.